Cost driven traffic assignment in transportation networks. (1st January 2013) - Dalalah, Doraid; Al-Rawabdeh, Wasfi A.
A cost driven traffic assignment model is proposed to maximise the global benefit of transportation network users. A decentralised primal-dual time synchronised approach is used to solve for the optimal traffic rates subjecting the objective function to the bounds of the network tolerable costs. For a successful operation of the transportation network, the affordable upper bounds on the costs have to be set carefully. A breakeven analysis was presented to estimate the network charges. It came across that the longer the route, the higher its charge. The breakeven surcharges represent the minimum quantities a network may charge from its commuters for a profitable operation. The presented scheme demonstrates a great control on the queue sizes and motivates resource allocation in heterogeneous transportation networks. The experimental results reveal an attractive convergence, performance and sensible resource assignment between the network users while achieving comprehensive optimality in a distributed approach.